2016
DOI: 10.1155/2016/6153215
|View full text |Cite
|
Sign up to set email alerts
|

MAPK Pathways Are Involved in Neuropathic Pain in Rats with Chronic Compression of the Dorsal Root Ganglion

Abstract: The aim of the present study was to investigate whether the MAPK pathways were involved in the mechanism of neuropathic pain in rats with chronic compression of the dorsal root ganglion. We determined the paw withdrawal mechanical threshold (PWMT) of rats before and after CCD surgery and then after p38, JNK, or ERK inhibitors administration. Western blotting, RT-PCR, and immunofluorescence of dorsal root ganglia were performed to investigate the protein and mRNA level of MAPKs and also the alternation in distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 32 publications
(30 reference statements)
3
34
0
Order By: Relevance
“…Our study demonstrated that the specific JNK activation inhibitor SP600125, ERK1/2 activation inhibitor UO126 and p38 activation inhibitor SB203580 significantly blocked the gene expression of IL-10 and POMC in cultured microglia. The results agree with previous findings in which each subtype of MAPKs was involved in the production of IL-10 in human alveolar macrophages and monocytes [7,28,29,39,58,63,64,93]. These results suggest that each ERK1/2, JNK, and p38 MAPK activation is associated with cinobufagin-induced expression of IL-10 after activation of α7-nAChRs.…”
Section: Discussionsupporting
confidence: 92%
“…Our study demonstrated that the specific JNK activation inhibitor SP600125, ERK1/2 activation inhibitor UO126 and p38 activation inhibitor SB203580 significantly blocked the gene expression of IL-10 and POMC in cultured microglia. The results agree with previous findings in which each subtype of MAPKs was involved in the production of IL-10 in human alveolar macrophages and monocytes [7,28,29,39,58,63,64,93]. These results suggest that each ERK1/2, JNK, and p38 MAPK activation is associated with cinobufagin-induced expression of IL-10 after activation of α7-nAChRs.…”
Section: Discussionsupporting
confidence: 92%
“…2b). The identified KEGG pathways in the ipsi cell body compartment have been associated with peripheral neuropathy 2933 or neuron growth and development 34, 35 .
Figure 2RNA-Seq analysis of enriched mRNAs in cell body and axon compartments. ( a ) Analysis of RNA-Seq reads processed by STAR aligner and DESeq2 revealed mRNA profiles in axon and cell body compartments of SNE ipsi and contralateral DRG neurons.
…”
Section: Resultsmentioning
confidence: 99%
“…MAPK pathways effectively attenuated SNL in rats with chronic compression of the dorsal root ganglion (Qu et al, 2016). Therefore, the GO function analysis results for the conjunct DEGs at 7th and 28th day after surgery suggested that MAPK pathways and Cox subunits may play a pivotal role in regulating the nociceptive transmission.…”
Section: Complicated Respondence Of Degs With Time After Surgerymentioning
confidence: 92%